Effect of zeolite particles towards corrosion rate on carbon steel in acid environment - Bambang Hari P; Hendriyana Hendriyana (Jurnal Sains Dasar, 2014)
The process of metal corrosion when it occurred can not be stopped, except with prevention. Corrosion is the deterioration or degradation of the metal due to a redox reaction between a metal with various substances in the environment that produce compounds that are not desired. In a simple term, also referred to as the corrosion of metal corrosion process dominated by steel or iron metal. The corrosion of the metal is a result of the oxidation reaction. Steel metal will produce rust generally in the form of oxides or carbonates. The chemical formula of iron rust is Fe2O3.nH2O in the form of a reddish brown solid. Zeolite is a mineral compound that can serve as an adsorber, cation exchange, and as a catalyst. In this study the ability of zeolite as anion or cation exchange adsorber will be measured. Its role is to be studied, especially in the environment in reducing hydrogen ions. The method used is by soaking and hanging the test object in a container that contains a solution of sulfuric acid and hydrochloric acid. The focus of this study is the reduction of the test object in the environment (some variations) such that the correlation can be calculated to determine the corrosion rate of mild steel specimen (mild steel). The environment is made as an acidic environment and acidic environment given zeolite particles. The results obtained on the test specimen immersion in acid medium with 1 N H2SO4 concentration and zeolite particles are used as much as 50g / 600 ml obtained in the immersion corrosion rate. Test specimens given stress are more quickly corroded. The rate of corrosion of steel which was given stress is 1.833 mpy and the corrosion rate of steel that was not given stress is 1.758 mpy. The addition of zeolite can reduce the corrosion rate by 15.20%. Key words: corrosion, zeolite, stress, mpy, adsorber